Partial nephrectomy and enbloc liver resection using a bipolar radiofrequency device for renal cell carcinoma invading the liver. (28th October 2010) - Pitchaimuthu, M; Pai, M; Habib, N A
Abstract : A 66-year-old man presented with right- sided abdominal pain. Ultrasound, CT and MRI scans showed a right renal mass arising from the upper pole with direct involvement of the right lobe of the liver. Biopsy confirmed renal cell carcinoma. After Multi Disciplinary Team (MDT) discussion, right partial nephrectomy with enbloc resection of segments VI and VII of the liver was performed with the help of intraoperative ultrasound scan and the Habib 4X bipolar radiofrequency device. Apart from symptomatic collection, which was drained radiologically, the patient made a good recovery. The patient developed recurrence at the resection margin but is in remission following chemotherapy at 12 months.